Tingkat Pengetahuan Keluarga Pasien terhadap Lampu Indikator di Ruang Radiologi di RSU Kertha Usada Buleleng - Genoveva Adventania Niron; Kadek Sukadana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Radiation protection is an action to reduce the impact of radiation arising from radiation exposure. Radiation sign lights are one of the requirements of x-ray aircraft facilities for radiation safety in hospitals intended for officers and the surrounding community in the radiology installation area. After the radiation indicator light is bright red and the door of the radiology examination room is closed, the patient's family is not allowed to enter so as not to be exposed to radiation or scattered radiation which has a very dangerous impact on health. The type of research used is a type of quantitative research using a descriptive method. This method aims to create an objective picture or descriptive description of a situation using numbers, starting from data collection, interpretation of the data as well as its appearance and results. The majority of respondents in this study were between 26 and 45 years old. The majority of respondents (78%) do not know about Indicator lights in the radiology room. Only (16%) or 8 respondents knew enough about the topic, and (6%) or 3 respondents knew it well. Based on the results of the study on